Pancreatic Beta-Cell Proliferation Induced by Estradiol-17β is Foxo1 Dependent - Shaklai, Sigal; Grafi-Cohen, Meital; Sharon, Orli; Sagiv, Nadav; Shefer, Gabi; Somjen, Dalia; Stern, Naftali (Hormone and Metabolic Research, 2018)
Estradiol-17β (E2) and the Foxo1 transcription factor have each been implicated in the regulation of β-cell proliferation. Interaction between Foxo1and estrogen receptor alpha (ERα), effecting cell cycle, has been demonstrated in breast cancer cells, but has not been studied thus far in β-cells. Using human islets and the INS1-E β-cell line, this study investigated the contribution of Foxo1 to E2-mediated β-cell replication. Foxo1 expression was knocked down in INS1-E cells using siRNA and Foxo1 activity was inhibited in human islets with a specific Foxo1 inhibitor (AS1842856). Cells were treated with E2 and the ERα agonist PPT and evaluated for proliferation by 3[H]-thymidine incorporation and for transcriptional activity through the estrogen response element by the luciferase assay. As Foxo1 activity is regulated by post-translational modifications, the effect of E2 on phosphorylation was also assessed. In INS1-E cells, knock down of Foxo1 abrogated the proliferative response to E2 and PPT. In human islets, inhibition of Foxo1 abrogated E2-mediated proliferation and attenuated the response to PPT. Foxo1 knock down and inhibition reduced activity through the estrogen response element by 25% (p<0.05) and 50% (p<0.01) respectively, in INS1-E cells. E2 increased Foxo1 phosphorylation in a time dependent manner in INS1-E and human islets (p<0.01, p<0.05, respectively). These findings suggest that Foxo1 is involved in E2-mediated proliferation in INS1-E cells and human islets. This may have implications vis-à-vis variations in circulating endogenous E2 concentrations in diabetes.
Keywords: estrogen; diabetes; replication